Proceedings of the 21st International Conference on Computational Linguistics and the 44th Annual Meeting of the ACL - ACL '06 2006
DOI: 10.3115/1220175.1220192
|View full text |Cite
|
Sign up to set email alerts
|

Relation extraction using label propagation based semi-supervised learning

Abstract: Shortage of manually labeled data is an obstacle to supervised relation extraction methods. In this paper we investigate a graph based semi-supervised learning algorithm, a label propagation (LP) algorithm, for relation extraction. It represents labeled and unlabeled examples and their distances as the nodes and the weights of edges of a graph, and tries to obtain a labeling function to satisfy two constraints: 1) it should be fixed on the labeled nodes, 2) it should be smooth on the whole graph. Experiment re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 14 publications
1
54
0
4
Order By: Relevance
“…Similarly as Chen et al (2006), who in turn followed Charniak (2000) and Zhang (2004), we experimented with additional constituency parse features describing grammatical functions and chunk tag information for all five contexts, and IOB-chains of the heads of the two entities. However, as preliminary experiments showed that these additional features do not provide any performance gains, we decided not to include them in our final models, intending to evaluate these results in future work.…”
Section: Svm Modelmentioning
confidence: 99%
“…Similarly as Chen et al (2006), who in turn followed Charniak (2000) and Zhang (2004), we experimented with additional constituency parse features describing grammatical functions and chunk tag information for all five contexts, and IOB-chains of the heads of the two entities. However, as preliminary experiments showed that these additional features do not provide any performance gains, we decided not to include them in our final models, intending to evaluate these results in future work.…”
Section: Svm Modelmentioning
confidence: 99%
“…Work conducted in [19] [20] employed semi-supervised learning algorithms and achieved good performance using only a small amount of labeled examples. They performed multi-class classification in which all the relation types are already defined [21].…”
Section: Related Workmentioning
confidence: 99%
“…Work conducted in [19] [20] performed multi-class relation classification [21] based on a hierarchical classification of relation types. However, relations to be extracted from Wikipedia are more fine-grained and diverse so that no such relation type classification is available in Wikipedia.…”
Section: Introductionmentioning
confidence: 99%
“…Further, due to the vast coverage of Wikipedia the extensions of the relations can be assumed to be relatively complete. Most of the above described datasets have been obtained from Wikipedia by automatically resolving category membership with the help of the CatScan 4 Tool by Daniel Kinzler. CatScan was applied iteratively to also obtain members of sub-categories.…”
Section: Datasetsmentioning
confidence: 99%
“…The methods include kernel-based methods [18,6] and graph-labeling techniques [4]. The advantage of such methods is that abstraction and partial matches are inherent features of the learning algorithm.…”
Section: Related Workmentioning
confidence: 99%